Business strategic alignment with Information Technology to increase organizational performance: study on banking sector - Kamruzzaman, Kamruzzaman; Anuar, Herman Shah (113 (2017), 2017)
IT-Business alignment has been consistently rated as one of the top ten IT management concern for last three decades. Theoretically, alignment can be defined as the degree of fit and combination between an organization’s IS (Information System) strategy and business strategy. More precisely, banks operates in a strategic Information System environment, where the alignment between IT and business should be significantly focused on organizational performance. However, this study suggests that technological innovation, strategic alignment, human resources are not an isolated source of improvement, but part of a system which mutually-reinforcing organizational performances. This research followed quantitative approach and survey questionnaire, so therefore, all 46 Bangladeshi bank (excluding foreign banks) were approached, a total number of 40 observations were usable and giving the study repose rate of 87%, which utilized for subsequent analysis. For this research, different type of analysis has been done, such as Factor analysis, Multiple-regression, t-test, ANOVA, where finding of the study is, technological innovation, strategic alignment and qualified human resources on organizational performance was identified to have a significant impact on organizational performances.